Inmate responses to correctional officer deviance: a model of its dynamic nature - Ross, Jeffrey Ian (Corrections, 2016)
The relationship between correctional officers (COs) and prisoners isdynamic and bounded by a unique context. COs engage in numeroussanctioned and unsanctioned behaviors within their correctional institu-tion. The latter actions are typically referred to as deviant behavior. COs’deviance can have a debilitating effect not only on other officers, correc-tional workers, the administration, but also inmates and the institution asa whole. This article specifies a model of the interaction between COs’deviance and inmate reactions to these kinds of behaviors. In general, thestudy argues that convicts can respond in four different, but interrelatedways: obedience or deference to authority, apathy, adaptation, and resis-tance. Acts of prisoners resisting can further lead to COs’deviant beha-viors to continue within the correctional institution.